Serological diagnosis of bovine, caprine, and ovine mastitis caused by Listeria monocytogenes by using an enzyme-linked immunosorbent assay. - Bourry, A (1997)
An enzyme-linked immunosorbent assay for detecting Listeria monocytogenes antibodies in bovine (n = 35), caprine (n = 27), and ovine (n = 30) milk samples was evaluated by comparison with bacteriological examination. Microtiter plates were coated with proteins obtained from culture supernatant, and antibodies were revealed with a monoclonal antibody able to react with the immunoglobulins belonging to the three animal species. The arithmetic mean optical density (OD) of milk samples infected with L. monocytogenes was above that of uninfected milk samples or milk samples infected with pathogens others than L. monocytogenes. With an OD threshold of 0.2 for goat and ewe milk samples, the sensitivity and specificity of the test were 100 and 88%, respectively. The choice of a different OD threshold (0.5) for cows allowed the discrimination of all of the infected cows and yielded no false positives, and both sensitivity and specificity were 100%.